Chaos in the Middle Zone: Nonperiodic Fluctuation in the Dynamic van Thunen Model - Kenneth A. Hansson (The Research Institute of Industrial Economics (IUI), 1985)
Non-periodic fluctuations of production activities are shown to exist in a dynamic von Thunen model for specific conditions of cost and demand.
Keywords: D24; L10; 330; Von Thunen model; production fluctuations; Raumwirtschaftstheorie